Valuasi Ekonomi Wisata Memancing di Perairan Laut Sekitar Tanjung Kait, Tangerang, Banten: Pendekatan Contingent Valuation Method dan Travel Cost Method: Economic Valuation of Recreational Fishing Tourism in Tanjung Kait Coastal Water, Tangerang, Banten: Contingent Valuation Method and Travel Cost Method Approach - Titan Budi Setyawan; Achmad Fahrudin; Handoko Adi Susanto (P4W LPPM IPB, 2020)
Economic Valuation of Recreational Fishing Tourism in Tanjung Kait Coastal Water, Tangerang, Banten: Contingent Valuation Method and Travel Cost Method Approach Tanjung Kait, located in the north coast of Tangerang, has undeveloped tourism potential of recreational fishing on a bamboo platform in the middle of the sea. The purpose of this research was to determine the economic value of recreational fishing tourism in Tanjung Kait and to identify the influencing factors of the tourism demand in Tanjung Kait. Methods used in this research were Travel Cost Method (TCM) and Contingent Valuation Method (CVM). Linear regression was used to determine influencing factors of tourism demand. Data were obtained by interviewing tourists as respondents, with the help of questionnaires. The result of TCM showed that factors that significantly contributed the number of visits were education and duration of visit. Potential economic value of tourism activity in Tanjung Kait based on TCM reached IDR 3,272,524,846 annually. The result of CVM showed that the factor that significantly affected willingness-to-pay was education. Potential economic value of tourism activity in Tanjung Kait based on CVM reached IDR 2,254,934,539 annually.